Insightful Quality - Sower, Victor (Business Expert Press, 2012)
Ebook from IG Library ; "This book is about how to think differently about quality and by doing so increase the creativity, innovation, and agility of an organization and its employees as well as the awareness of new developments in the marketplace and their possible impact on the organization and its markets. Quality must be addressed in strategic as well as operational terms in order for organizations to compete effectively over the long term. Strategic quality management requires insightful leadership."